2019
DOI: 10.1007/s11469-019-00192-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment-Seeking Problem Gamblers: Characteristics of Individuals Who Offend to Finance Gambling

Abstract: The relationship between crime and gambling is well established; however, few studies have examined offending specifically to finance gambling within a UK gambling treatment-seeking population. A total of 1226 treatment-seeking gamblers completed the Problem Gambling Severity Index (PGSI), Patient Health Questionnaire and the Generalized Anxiety Disorder 7 item scale, and were asked whether they had committed any illegal behaviours to finance gambling. A total of 42.5% reported offending behaviour. A greater p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 56 publications
(67 reference statements)
4
5
0
Order By: Relevance
“…These findings are largely generally in keeping with previous data 3,[7][8][9][10][11][12] although we did not find that most measures of gambling severity differed between groups nor did the SDS differ. Unlike previous studies, however, this study found that poorer quality of life was associated with illegal behaviors.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These findings are largely generally in keeping with previous data 3,[7][8][9][10][11][12] although we did not find that most measures of gambling severity differed between groups nor did the SDS differ. Unlike previous studies, however, this study found that poorer quality of life was associated with illegal behaviors.…”
Section: Discussionsupporting
confidence: 93%
“…10 Gamblers with a history of illegal behavior tend to be younger, have more severe gambling disorder symptoms, greater gambling debt, lower income, experienced childhood abuse, report family mental health problems and gambling-related harms, and are more likely to meet criteria for antisocial personality disorder than gamblers who do not have gambling-related criminal behaviour 3,11,12 Gambling-related illegal behaviors also appear to be associated with an elevated risk of suicidal ideation, financial problems, and alcohol and drug use. 11,12 Although the data on gambling-related illegal behaviors are limited, these studies suggest that illegal behaviors may have associations with both gambling symptom severity and psychosocial impairment associated with gambling disorder. This in turn may suggest that different services or different intensities of services may be necessary for people with gambling disorders who report illegal behaviors associated with their gambling.…”
Section: Introductionmentioning
confidence: 99%
“…Participant LP6, LP7, and LP9 stated: "when faced with the facts of gambling evidence, he became verbally abusive toward me, and threatened me." Similar results are found in the studies byRoberts et al (2019), indicating that problem gambling and family violence were common.…”
supporting
confidence: 89%
“…Thus, the pathological gamblers posed abusive risks to their family members due to their lack of emotional control and extensive substance abuse (Jauregui et al, 2015). The same results derived from the study conducted by Roberts et al (2019), using a sample of 1226 treatment-seeking gamblers, using a survey index, where gambling and criminality are related.…”
Section: Abusive Behaviorsmentioning
confidence: 52%
“…There is growing recognition of the adverse consequences of gambling, which may comprise vocational disruptions (e.g., job loss; Langham et al, 2015), deviant and criminal behaviour (Roberts, Sharman, King, Bayston, & Bowden-Jones, 2019), as well as severe financial problems (Grant, Schreiber, Odlaug, & Kim, 2010), mental health issues (Krause et al, 2018), and interpersonal difficulties (Roberts et al, 2018). The increasing awareness of the magnitude of these issues has provided impetus for initiatives to reduce maladaptive gambling and associated harms (Public Health England, 2020).…”
Section: Introductionmentioning
confidence: 99%